Pharmacological Investigations in Glia Culture Model of Inflammation - Ismail, Fatme Seval; Corvace, Franco; Faustmann, Pedro M.; Faustmann, Timo Jendrik (Frontiers in Cellular Neuroscience, 2021)
Astrocytes and microglia are the main cell population besides neurons in the central nervous system (CNS). Astrocytes support the neuronal network via maintenance of transmitter and ion homeostasis. They are part of the tripartite synapse, composed of pre- and postsynaptic neurons and perisynaptic astrocytic processes as a functional unit. There is an increasing evidence that astroglia are involved in the pathophysiology of CNS disorders such as epilepsy, autoimmune CNS diseases or neuropsychiatric disorders, especially with regard to glia-mediated inflammation. In addition to astrocytes, investigations on microglial cells, the main immune cells of the CNS, offer a whole network approach leading to better understanding of non-neuronal cells and their pathological role in CNS diseases and treatment. An in vitro astrocyte-microglia co-culture model of inflammation was developed by Faustmann et al., 2003, which allows to study the endogenous inflammatory reaction and the cytokine expression under drugs in a differentiated manner. Commonly used antiepileptic drugs (e.g., levetiracetam, valproic acid, carbamazepine, phenytoin, gabapentin), immunomodulatory drugs (e.g., dexamethasone, interferon-beta), hormons and psychotropic drugs (e.g., venlafaxine) were already investigated, contributing to better understanding mechanisms of actions of CNS drugs and their pro- or anti-inflammatory properties concerning glial cells. Furthermore, the effects of drugs on glial cell viability, proliferation and astrocytic network were demonstrated. The in vitro astrocyte-microglia co-culture model of inflammation proved to be suitable as unique in vitro model for pharmacological investigations on astrocytes and microglia with future potential (e.g., cancer drugs, antidementia drugs, toxicologic studies).